2021
DOI: 10.37939/jrmc.v25i3.1569
|View full text |Cite
|
Sign up to set email alerts
|

Role of Occiput Spinal Angle-A Novel Sonographic Index to predict the outcome of labour

Abstract: Introduction: The attitude (relationship of head of a fetus to the cervical spine) in the first stage of labour has a significant impact on the outcome of labour. Deflexion of the fetal head is determined by digital vaginal examination during labour. However, different ultra-sonographic indexes have been developed to predict labour outcomes. Occiput spine angle (OSA) is a novel ultra-sonographic marker which can be used to predict operative delivery. Objective: To determine the effect of the occipital sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…While, Mughal et al 19 demonstrated that OSA had a sensitivity and specificity of 92% and 98% respectively for prediction of operative birth.…”
Section: Mode Of Deliverymentioning
confidence: 98%
“…While, Mughal et al 19 demonstrated that OSA had a sensitivity and specificity of 92% and 98% respectively for prediction of operative birth.…”
Section: Mode Of Deliverymentioning
confidence: 98%